Measuring service quality using SERVQUAL model: An overview on customers satisfaction of online shopping in Malaysia - Ariffin, Ahmad Shabudin; Mohtar, Shahimi; Ibrahim, Amlus; Amlus, Mohamad Harith (2012)
Since the difficulties in both defining and measuring it with no overall consensus emerging on either, service quality is a concept that has aroused significant interest and debate in the research literature.Customer satisfaction and service quality are often treated together as functions of customer’s perceptions and expectations and research has revealed that high service quality contribute significantly to profitability.Service quality is requisite to be first measured in order to improve the quality in a service organization.Practitioners and academics are keen on measuring service quality accurately in order to have better understanding of its essential antecedent and consequences, and eventually establish methods for improving and measuring service quality in search for competitive advantage. The aim of this study is to get the previous research finding of service quality that affects the customers’ expectation in online purchasing from the customers’ perspective. The measurements used were based on the widely accepted SERVQUAL model which is the most common method for measuring service quality.